Benchmarking adoption of e-commerce across the G20 members - Tanu M. Goyal; Peter J. Morgan (Asian Development Bank Institute (ADBI), 2023)
The COVID-19 situation has accelerated the adoption of e-commerce across the world. While, globally, there has been an increase in the share of e-commerce in total retail sales, there are variations in e-commerce adoption across countries and the difference is obtrusive when one compares developed countries and emerging market economies. This paper undertakes a comparative assessment of e-commerce adoption by the G20 countries and, in doing so, it benchmarks the G20 members across different indicators that determine e-commerce adoption. Based on secondary data, the paper presents some stylized facts, discusses the regulatory scenario with respect to e-commerce in G20 countries and identifies key constraints to e-commerce adoption in the comparatively poor performers. It is found that, overall, most emerging market economies are not very well prepared to support e-commerce adoption. Rather, compared to the developed countries, emerging market economies perform poorly on indicators related to access and use of digital technology, financial inclusion, postal reliability, and electronic security. The paper found that the emerging market economies are severely affected by inadequate infrastructure, digital illiteracy, and low use of digital payments by enterprises. Whereas there is no dearth of regulations on e-commerce business, nevertheless a uniform approach for regulating e-commerce operations is missing in the case of some countries. Moreover, different countries have different positions with respect to data privacy and protection. The paper recommends that G20 members should work together to bridge the adoption gap, enhance micro, small and medium enterprises (MSMEs) participation in e-commerce through enhanced financial assistance, build cooperation for adopting common standards, and encourage countries to adopt national policies with the vision to promote e-commerce.
Keywords: F02; F42; F53; G53; L81; 330; MSME; G20; digital; e-commerce